Case report: a child with type 1 neurofibromatosis and intellectual disability - Elice Wijaya; Ni Luh Putu Ratih Vibriyanti Karna; Ida Ayu Uttari Priyadarshini (Bali Dermatology Venereology and Aesthetic Journal, 2021)
Background: Neurofibromatosis is a genetic disorder that manifests as a tumor surrounding the nerves and several other pathologic presentations. Case: Female, 11 years old, according to history, physical examination and supporting the investigation, was consistent with the diagnostic criteria of type 1 neurofibromatosis (NF-1). The patient also has an intellectual disability. A tumor on the foot region that was functionally disabling was found on the patient, and surgical treatment was performed. Cognitive disorder is the most common neurological complication in individuals with NF-1 and usually presents with a low intelligence quotient (IQ). There is no specific treatment to prevent the development of NF-1. However, early treatment can minimize and prevent further complications. Treatment for the patient involves multiple clinical disciplines. Conclusion: A neurofibromatosis case can be diagnosed clinically alone, since many other systemic involvements require a multi-disciplinary approach.